IMPROVEMENT OF SUBSTANTIVE PROVISIONS OF THE VALIDITY OF AGREEMENT IN THE INDONESIAN CIVIL CODE - Natasya Yunita Sugiastuti; Dian Purnamasari (Diponegoro Law Review, 2023)
The legal effect of non-fulfillment of the requirement for the validity of the agreement is that the existence of such agreement is not recognized, cancellation can be requested or it can be declared null and void. Due to the significance of such legal requirements and consequences for the validity of the agreement, it is in need of analysis. With the emergence of the idea of reforming national contract law, this research intends to provide some thoughts for the improvement of the national law of obligations, particularly with regard to the validity of the agreement. These reflections are results of the study regarding to contract validity as regulated under Nieuw Burgerlijk Wetboek. This is normative legal research; with the legislative, conceptual, and comparative law approach, the data used is in the form of secondary data, obtained through a literature review. Based on the results of the study, several recommendations are being put forward for the improvement of the national law of obligations, both with regard to the subjects entering into agreement (provisions concerning consent and capacity) as well as recommendations with regard to the object of agreement (provisions concerning certain things and the contents of agreement).